The Influence of the Teams Games Tournament Learning Model Using Educaplay Media on Elementary School Students' Understanding of Landscape Concepts - Tiara Tri Akhliah; Mustamiroh; Iksam; Hety Diana Septika (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Students' comprehension abilities in Social Science Studies at SDN 008 Samarinda Ilir are satisfactory because learning is dominated by conventional methods, making students more passive and easily bored. This condition requires the implementation of innovative, interactive, and enjoyable learning models. The TGT model combined with the digital media Educaplay is considered to be capable to increase students' motivation, participation, and understanding through a combination of group work and game-based learning. This research aims to determine the effect of the TGT learning model by using Educaplay on the understanding ability of third-grade students at SDN 008 Samarinda Ilir for the 2024/2025 academic year. The research used a quantitative method by using a One Group Pretest-Posttest Design. The sample included 27 students selected by the purposive sampling technique. Data was collected through 20 multiple-choice questions, given before and after the treatment, then analyzed with a paired samples t-test by using SPSS version 27. The research results indicate that the average pretest score was getting 55 score that increased to 69.44 score on the posttest, with a significance level of 0.000 < 0.05. It can be concluded that the TGT model assisted by Educaplay significantly influences students' understanding abilities in IPAS and effectively creates active, enjoyable, and meaningful learning